Teknik Role Playing untuk Meningkatkan Kepercayaan Diri Siswa SMP - Deasy Yunika Khairun; Ibrahim Al Hakim; Ninis Solihah (Indonesian Journal of Educational Counseling, 2020)
ROLE PLAYING TECHNIQUES TO INCREASE THE CONFIDENCE OF MIDDLE SCHOOL STUDENTS. The purpose of this research was to saw the influenced of role playing techniques on student’s self-confidence. This study used a pre-experimental method with one group pre-post-test design. The study population was 173 students and the research sample was taken using purposive sampling, in which as many as 12 students from class IX SMPN 10 Serang City. Data collection techniques use student’s confidence instruments. The results of the study show that role playing techniques could have an effective on increasing the confidence of IX SMPN 10 Serang City. Role playing techniques have an effect on increasing student confidence.